Ustekinumab trough levels in children with Crohn’s disease refractory to anti-tumor necrosis factor agents: a prospective case series of off-label use - Bouhuys, Marleen; Mian, Paola; van Rheenen, Patrick F. (Frontiers in Pharmacology, 2023)
Background: Ustekinumab is used off-label in pediatric Crohn’s disease refractory to anti-tumor necrosis factor. Data on optimal dosing, target trough levels, and potential benefit of therapeutic drug monitoring in children treated with ustekinumab are limited. Materials and Methods: We describe a series of six adolescents who consented to be treated with ustekinumab. We measured their trough levels, C-reactive protein, and fecal calprotectin before every administration. Results: Standard adult dosing was effective to achieve biochemical remission (fecal calprotectin < 250 mg/kg) in one patient and clinical remission (resolution of symptoms) in another. The other four patients failed to respond on standard dosing and underwent intravenous re-induction and interval shortening to increase ustekinumab trough levels. This resulted in biochemical remission in one patient and clinical remission in another, suggesting an exposure–response relationship. The remaining two patients had no therapeutic benefit, and ustekinumab was discontinued. Conclusion: In this report, we show that ustekinumab can induce remission in pediatric patients with anti-tumor necrosis factor refractory Crohn’s disease. It is worth escalating the dose before abandoning the drug as ineffective. Prospective studies in children are needed to determine long-term efficacy of ustekinumab, usefulness of therapeutic drug monitoring strategies, and, if applicable, optimal target trough levels.